2004
DOI: 10.1128/jb.186.1.29-34.2004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Growth Temperature on Lipid and Phosphate Contents of Surface Polysaccharides from the Antarctic Bacterium Pseudoalteromonas haloplanktis TAC 125

Abstract: The chemical structural variations induced by different growth temperatures in the lipooligosaccharide and exopolysaccharide components extracted from the Antarctic bacterium Pseudoalteromonas haloplanktis TAC 125 are described. The increase in phosphorylation with the increase in growth temperature seems to be general, because it happens not only for the lipooligosaccharide but also for the exopolysaccharide. Structural variations in the lipid components of lipid A also occur. In addition, free lipid A is fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 21 publications
3
64
1
Order By: Relevance
“…But several phenotypic markers are variable and dependent on environmental cues. For instance, the expression of characteristics that serve in genus description, such as cell morphology [39][40][41][42], enzymes [43,44], fatty acids [45,46] menaquinones [47][48][49], lipids [50][51][52][53] and peptidoglycan [54][55][56][57], depend on the growth conditions. Further, discrepancies in the above traits were well documented among species of several genera [58,59], and thus hamper in drawing congruence between phylogeny and expressed characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…But several phenotypic markers are variable and dependent on environmental cues. For instance, the expression of characteristics that serve in genus description, such as cell morphology [39][40][41][42], enzymes [43,44], fatty acids [45,46] menaquinones [47][48][49], lipids [50][51][52][53] and peptidoglycan [54][55][56][57], depend on the growth conditions. Further, discrepancies in the above traits were well documented among species of several genera [58,59], and thus hamper in drawing congruence between phylogeny and expressed characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] Because microorganisms are at thermal equilibrium with their environment, it is reasonable to assume that structural and functional components in psychrophiles (optimal growth at ≤ 15°C) have adapted, to some degree, to the requirements of a low temperature existence, 4 including the possible presence of ice crystals in their immediate surroundings. The reported mechanisms of bacterial adaptation to low temperature include the over-expression of cold-shock and heat-shock proteins, the presence of unsaturated and branched fatty acids that maintain membrane fluidity, 5 the different phosphorylation of membrane proteins and lipopolysaccharides, [6][7][8][9][10][11] and the production of cold-active enzymes, 12 antifreeze proteins and cryoprotectants. 13 The latter are chemical substances that generally include small molecules, such as glycine betaine, some amino acids, sugars (glucose, fructose) and sugar alcohols (mannitol, glycerol).…”
Section: Introductionmentioning
confidence: 99%
“…20 Despite their important roles in cryoprotection and environmental interactions, few exopolysaccharide structures from cold-adapted bacteria have been accurately elucidated. 7,19,21 In addition, an increased understanding of the structural characteristics of these polymers is a prerequisite to potential biotechnological exploitation of cold-adapted bacterial EPS. Colwellia psychrerythraea 34H is a Gram-negative bacterium belonging to the phylum γ-proteobacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Corsaro et al (25), have suggested that the psychrophile Pseudoalteromonas haloplanktis TAC125 is unable to complete the biosynthesis of lipooligosaccharide at a suboptimal temperature as the phosphorylation of both lipooligosaccharide and EPS decreases with temperature. In these molecules, phosphate groups bind to divalent cations, such as Ca 2ϩ and Mg 2ϩ , stabilizing the extracellular leaflet of the outer membrane (50,76) and modulating its permeability.…”
Section: Ii) Cell Envelope Biogenesis and Outer Membrane (Class M) (Smentioning
confidence: 99%
“…Workers have speculated about the involvement of capsular polysaccharide in adaptation to low temperature for some time (25,60,62). FL26 contains a disruption in the gene encoding the PBPRA0218 protein, a predicted O-antigen ligase for lipopolysaccharide (LPS) synthesis whose expression is reduced at low temperature (19,87).…”
Section: Vol 190 2008mentioning
confidence: 99%